SISTEM KONTROL DAN MONITORING TANAMAN HIDROPONIK SECARA REAL TIME MENGGUNAKAN METODE FUZZY INFERENCE SYSTEM MODEL TSUKAMOTO - Rizaldy Setiawan Hasanuddin; Isnawaty Isnawaty; Rizal Adi Saputra; Statiswaty Statiswaty (semanTIK, 2019)
The hydroponic plant is the technique of cultivating plants (fruits, vegetables, and flowers) by utilizing water and not using soil as a planting medium. Internet of Things (IoT) is the communication between one device and another with the help of software through the internet network. The one method for controlling IoT is using Fuzzy Tsukamoto. The Tsukamoto method is an extension of monotonous reasoning.In Tsukamoto's method, each consequence of  If-Then form rule must be represented by a fuzzy compilation with an affiliation function. The advantages of Fuzzy Tsukamoto system are the mathematical concepts that underlie fuzzy reasoning is very simple and easy to understand. In applying  Fuzzy Tsukamoto in the determination of control and monitoring of hydroponic plants in real-time-based, it functions very efficiently and simplifies work. Keywords—Hydroponic Plants, IoT, Fuzzy Tsukamoto.DOI : 10.5281/zenodo.2781533